2016
DOI: 10.1186/s12885-016-2126-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of receptor for advanced glycation endproducts on microvessel formation in endometrial cancer

Abstract: BackgroundThe receptor for advanced glycation endproducts (RAGE) and microvascular status both play a critical role in cancer progression. However, the crosstalk between RAGE and microvascular formation in endometrial cancer remains largely unknown.MethodsRAGE expression and microvessel density were examined in 20 cases of normal endometrial tissue, 37 cases of well-differentiated endometrial cancer tissue, and 35 cases of poorly-differentiated endometrial cancer tissue. Regression analysis was used to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
2
9
2
Order By: Relevance
“…AGER-deficient mice presented a decreased tendency for breast tumor growth [ 8 ] and AGER gene deletion inhibited the development of pancreatic intraepithelial neoplasia and progression to pancreatic ductal adenocarcinoma in a murine model [ 23 ]. Similar results were reported in endometrial cancer [ 15 ], colorectal cancer [ 18 ], and prostate cancer [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…AGER-deficient mice presented a decreased tendency for breast tumor growth [ 8 ] and AGER gene deletion inhibited the development of pancreatic intraepithelial neoplasia and progression to pancreatic ductal adenocarcinoma in a murine model [ 23 ]. Similar results were reported in endometrial cancer [ 15 ], colorectal cancer [ 18 ], and prostate cancer [ 24 ].…”
Section: Discussionsupporting
confidence: 86%
“…It plays decisive roles in diverse processes including inflammation and cancer [ 9 , 10 ]. AGER has been widely reported to be overexpressed in ovarian cancer [ 12 ], breast cancer [ 13 ], gastric cancer [ 14 ], colorectal cancer [ 21 ], and endometrial cancer [ 15 ]. With regard to cervical cancer, Xu et al [ 22 ] reported that AGER 82G>S polymorphisms were associated with significantly elevated risk of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGER is one of a limited number of pathogen recognition receptors whose expression is downregulated in lung cancer (Rho, Roehrl, & Wang, 2009;Wang, Li, Yu, et al, 2015). However, AGER has been widely reported being highly expressed in various types of cancer, including ovarian cancer (Rahimi et al, 2017), breast cancer (Nankali et al, 2016), gastric cancer (Wang, Li, Ye, et al, 2015), and endometrial cancer (Zheng et al, 2016). In the current study, we found AGER was significantly and consistently downregulated at least 8.266-fold in LUAD according to four independent microarrays databases.…”
Section: Discussionmentioning
confidence: 99%
“…Contribution of surface receptor RAGE signaling is an additional component contributing to endometrial microenvironment [ 25 , 26 , 27 ]. This is a transmembrane receptor expressed on several cell types, including epithelial, endothelial, and immune cells activating migration, proliferation, and inflammatory response [ 26 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%